OTORITAS KEAGAMAAN DAN FATWA PERSONAL DI INDONESIA - Muzakka, Ahmad Khotim (EpistemÃƒÂ©: Jurnal Pengembangan Ilmu Keislaman, 2018)
Fatwas are not only produced by a religious institution such as the Indonesian Ulama Council (MUI), Nahdlatul Ulama and Muhammadiyah but also by a religious leader nowadays. The use of social media and websites makes more easily for a religious leader to spread out their own opinion. People, now, are more interconnected with each other. Religious experts spread their religious views through personal websites an even through social media. Through their personal websites, Indonesian Muslim intellectuals Nadirsyah Hosen and Firandaâfor exampleâuse their personal websites to spread their religious ideas. It is interesting to read both views of this character because they both have a different educational background. Nadirsyah Hosen was graduated from Western University, while Firanda was educated in Saudi Arabia. This article dissects on some of these questions: Using content analysis methods, this study answers some questions; what are their concerns? How do contemporary issues influence their religious views? The study finds that both use a variety of scientific arguments based on various literature. At some level, Nadirsyahtries to combine classical and modern literature, while Firanda focuses on the use of classical literature. Each of these approaches has implications for their personal ideas.